Sphingosylphosphorylcholine inhibits plasma cell differentiation and ameliorates experimental autoimmune encephalomyelitis - Byunghyun Park; Yu Sun Jeong; Wonseok Hu; Mingyu Lee; Ji Cheol Kim; Geon Ho Bae; Yong-Soo Bae; Yoe-Sik Bae; Yoe-Sik Bae (Frontiers in Immunology, 2023)
IntroductionMultiple sclerosis (MS) is a potentially disabling disease that damages the brain and spinal cord, inducing paralysis of the body. While MS has been known as a T-cell mediated disease, recent attention has been drawn to the involvement of B cells in its pathogenesis. Autoantibodies from B cells are closely related with the damage lesion of central nervous system and worse prognosis. Therefore, regulating the activity of antibody secreting cell could be related with the severity of the MS symptoms.MethodsTotal mouse B cells were stimulated with LPS to induce their differentiation into plasma cells. The differentiation of plasma cells was subsequently analyzed using flow cytometry and quantitative PCR analysis. To establish an experimental autoimmune encephalomyelitis (EAE) mouse model, mice were immunized with MOG35–55/CFA emulsion.ResultsIn this study, we found that plasma cell differentiation was accompanied by upregulation of autotaxin, which converts sphingosylphosphorylcholine (SPC) to sphingosine 1-phosphate in response to LPS. We observed that SPC strongly blocked plasma cell differentiation from B cells and antibody production in vitro. SPC downregulated LPS-stimulated IRF4 and Blimp 1, which are required for the generation of plasma cells. SPC-induced inhibitory effects on plasma cell differentiation were specifically blocked by VPC23019 (S1PR1/3 antagonist) or TY52159 (S1PR3 antagonist), but not by W146 (S1PR1 antagonist) and JTE013 (S1PR2 antagonist), suggesting a crucial role of S1PR3 but not S1PR1/2 in the process. Administration of SPC against an EAE mouse model significantly attenuated the symptoms of disease, showing decreased demyelinated areas of the spinal cord and decreased numbers of cells infiltrated into the spinal cord. SPC markedly decreased plasma cell generation in the EAE model, and SPC-induced therapeutic effects against EAE were not observed in μMT mice.ConclusionCollectively, we demonstrate that SPC strongly inhibits plasma cell differentiation, which is mediated by S1PR3. SPC also elicits therapeutic outcomes against EAE, an experimental model of MS, suggesting SPC as a new material to control MS.